Avaliação hidrodinâmica de um reator anaeróbio de leito fixo tratando esgotos sanitários - Baettker, Ellen Caroline (2012)
The objective of this Completion of Course Work was to evaluate the performance of an anaerobic fixed channel reactor with polyurethane foams and expanded clay as a medium for the treatment of sewage. For this, a bench scale reactor (6.2 L) was operated with influent flow rate of 0.6 L.h-1 and HRT of 8 h and maintained at room temperature. The behavior of the reactor was evaluated by determining the physico-chemical parameters temperature, pH, total and partial alkalinity, bicarbonate, volatile acids, COD (raw and filtered), total solids (fixed and volatile) and suspended solids (fixed and volatile). Further, tests were performed stimulus-response type pulse with eosin Y, blue bromophenol and green bromocresol to evaluate the hydrodynamic regime of the reactor and verification of anomalies in the hydrodynamic behavior. The results indicated that the sewage can be classified as "strong" in terms of COD and total solids according to Metcalf and Eddy (2003). The microscopic examinations were performed during the inoculation to assess the microbiota present in the reactor. Among the bacteria, the morphologies observed were more coconuts, vibrios, rods and filaments. The average values of temperature, pH, were 24.9 ± 6.9 and 24.0 ±7.4 effluent. The concentrations of bicarbonate alkalinity were 131 and 188 mgCaCO3.L-1 respectively influent and effluent. Volatile acids in the effluent resulted in values below 76 mgHac.L-1. The medium efficiency of removal of COD gross ranged from 84% to 52% and filtered COD of 65% to 27%. The average concentrations of ST were 1395 mg.L-1 for the affluent and of 391 mg.L-1 for the effluent. The average concentrations were TSS 587 mg.L-1 for the influent and 216 mg.L-1 for the effluent. In tests of hydrodynamic phenomena trail observed in the curves obtained results from the diffusion of the tracer in dead zones and its slow release in the effluent. For the calculation of dead zones was obtained negative values due to the presence of preferential paths. The presence of short circuits has barely been seen in hydrodynamic tests except 3 of green bromocresol. In the study of hydraulic efficiency was found that in almost all tests have resulted in poor hydraulic efficiency (λ≤0.5) for constant flow, except in trial 1 blue bromophenol and 2 green bromocresol.